Time-of-Day-Dependent Effects of Aerobic Exercise on Carotid Hemodynamics in Sedentary Adults - Bingyi Shen; Haibin Liu; Shuying Zhang; Lihong Chen; Guangrui Yang (Biology)
Aerobic exercise (AE) modulates vascular function through hemodynamic responses, thereby influencing cardiovascular health and risk, with the circadian rhythm system playing a crucial role. This chronobiological study investigated diurnal variations in exercise-induced hemodynamic changes in the common carotid artery. In a randomized crossover trial, twenty-two sedentary adults completed eight AE interventions (one per laboratory visit day), with each session performed at one of eight evenly distributed time points (from 06:00 to 20:00). Vascular ultrasound imaging and hemodynamic parameter calculations were performed both pre- and post-exercise. Compared to other time points, AE at 06:00 and 18:00 induced a greater and more sustained increase in mean flow rate and wall shear stress (WSS). Moreover, AE at 06:00 was associated with a smaller increase in oscillatory shear index and a larger decrease in peripheral resistance compared to other time points. Exercise-induced hemodynamic responses exhibited significant temporal variations. These findings emphasize the importance of exercise timing in optimizing vascular benefits for sedentary individuals.